2009
DOI: 10.5004/dwt.2009.709
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration membrane cleaning with different chemical solutions after treating surface water

Abstract: In recent years, application of pressure-driven membrane processes as ultrafiltration (UF) has expanded as an alternative promising technology to obtain drinking water for human consumption. Despite the strong potential of membranes, one of the common problems encountered in applications is membrane irreversible fouling. AQUAPOT project faces this common problem in the spiral-wound UF facilities that are located in Ecuador and Mozambique. Lack of chemicals and application of not optimized cleaning protocols ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…FTIR, SEM and EDX analysis done to the UF membrane proved that the membrane surface was covered with a compact gel layer formed by organic substances and inorganic elements such as Mg, Al, Ca, Si or Fe coming from the surface water that caused irreversible fouling [32].…”
Section: Cleaning Strategies Under the Scope Of The Aquapot Projectmentioning
confidence: 99%
See 4 more Smart Citations
“…FTIR, SEM and EDX analysis done to the UF membrane proved that the membrane surface was covered with a compact gel layer formed by organic substances and inorganic elements such as Mg, Al, Ca, Si or Fe coming from the surface water that caused irreversible fouling [32].…”
Section: Cleaning Strategies Under the Scope Of The Aquapot Projectmentioning
confidence: 99%
“…Dynamic test [32] performed after static test, revealed that best cleaning solutions were Sodium hypochlorite at 25 ºC, Hydrogen Peroxide at 25 and 40 ºC and Auxiclean B. 13 at 25 and 40 ºC after 2 hour cleaning.…”
Section: Cleaning Strategies Under the Scope Of The Aquapot Projectmentioning
confidence: 99%
See 3 more Smart Citations